Macroeconomics, Enhanced Global Edition - Blanchard, Olivier (Pearson International Content, 2020)
For intermediate courses in economics.   In Macroeconomics, Blanchard presents an integrated, global view of macroeconomics, enabling students to see the connections between goods markets, financial markets, and labor markets worldwide.   A unified view of the latest macroeconomic events In Macroeconomics, Blanchard presents an integrated, global view of macroeconomics, enabling students to see the connections between goods markets, financial markets, and labor markets worldwide. Organized into two parts, the text contains a core section that focuses on short-, medium-, and long-run markets and two major extensions that offer more in-depth coverage of the issues at hand. From the major economic crisis that engulfed the world in the late 2000s, to monetary policy in the US, to the problems of the Euro area, and growth in China, the text helps students make sense not only of current macroeconomic events but also of those that may unfold in the future. Integrated, detailed boxes in the 8th Edition have been updated to convey the life of macroeconomics today, reinforce lessons from the models, and help students employ and develop their analytical and evaluative skills.